Effect of electrolyzed water on physicochemical and sensory qualities of beef - G. Biswas; Md. S. Islam; S. M. M. Rahman; S. M. A. Al Mamun (Теория и практика переработки мяса)
During beef processing, contamination by microorganisms from diverse sources poses a significant risk to its quality and safety. This contamination can lead to reduced shelf life, compromised meat quality, and increased health hazards. In recent years, electrolyzed water (EW) has emerged as a promising solution for sanitizing and cleaning beef. The purpose of this study was to evaluate the physicochemical and sensory qualities of beef that had been treated with EW. In this experiment, there were three replications with a factorial Randomized Complete Block Design (RCBD). Factor-A: consisted of six (06) treatments concentrations: T0 = Control sample (fresh water); T1 = 10 ppm electrolyzed water; T2 = 20 ppm electrolyzed water; T3 = 30 ppm electrolyzed water; T4 = 40 ppm electrolyzed water; T5 = 50 ppm electrolyzed water; Factor-B: consisted of three (03) durations: TM1 = 5 minutes; TM2 = 10 minutes; TM3 = 15 minutes. The findings showed that the moisture content (%), crude protein (%), ether extract (%) and ash content (%) of beef samples ranged from 72.31 ± 0.29 to 73.93 ± 0.30, 19.95 ± 0.16 to 21.91 ± 0.19, 4.28 ± 0.09 to 5.06 ± 0.09, 1.29 ± 0.09 to 1.76 ± 0.07 respectively. Beef's proximate composition (moisture, crude protein, ether extract, dry matter, and ash) and physical analyses (cooking yield, cooking loss, and pH) were not significantly affected by the EW treatments (p > 0.05). However, drip loss and beef color showed substantial significant effects (p < 0.05). Findings suggest that EW treatments with concentration up to 50 ppm can effectively decontaminate beef while maintaining its nutritional and sensory properties.